Reasonable minimum sealing length of in-seam boreholes for coal mine methane drainage: a case study. Issue 18 (16th September 2020) - Wang, Kai; Lou, Zhen; Wei, Guoying; Lu, Weidong; Du, Feng; Qin, Binbin
ABSTRACT: Coal mine methane (CMM) drainage is an effective method to curb the occurrence of coal and gas outburst and gas explosion, to reduce the amount of greenhouse gas emission, and to make full use of the clean energy(methane). Sealing in-seam horizontal boreholes plays a vital role in CMM drainage. Reasonable sealing length is an important factor to achieve high extraction efficiency and reduce the cost of construction. To determine the minimum reasonable sealing length of drainage boreholes, the radius of the fracture zone was obtained based on the ideal elastoplastic model, and this radius was taken as the minimum sealing length. The influencing factors of the minimum sealing length were analyzed and engineering verification test was taken in Zhongmacun mine in Henan province, China. The research results show that the minimum reasonable sealing length should be longer for a larger radius of the coal roadway and the coal seam with a deeper buried depth, while the minimum reasonable sealing length can be shortened with the increase of uniaxial compressive strength and the supporting stress of the coal roadway. The 11.07 m of sealing length calculated by theories was basically consistent with the 12 m of sealing length verified by the method of drilling cuttings. The reasonableness of sealing length (12 m) was verified by the test results of methane concentration and flux within 40 days. All those outcomes can provide references for other mines to determine the minimum reasonable sealing length of in-seam boreholes for CMM drainage.